2020
DOI: 10.1155/2020/4757065
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of miR-181b and IFNA1 Polymorphisms on the Risk of Systemic Lupus Erythematosus

Abstract: Introduction. A previous work has discovered that chromosome 1q32 locus linked to the risk of systemic lupus erythematosus (SLE) and miR-181b located on the susceptibility site with downregulation inversely correlating to its target molecular interferon alpha 1 (IFNA1). The purpose of this study was to investigate the association of miR-181b and IFNA1 polymorphisms with IS risk. Methods. The miR-181b rs322931, IFNA1 rs1332190, and rs10811543 were genotyped using a Multiplex SNaPshot assay. miR-181b expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Although IFNA1 rs1332190 and rs10811543 alone were not significantly related to SLE, a combined analysis of these three factors simultaneously augmented the risk of disease progression. Therefore, He et al , 109 finding a correlation between miR-181b expression and rs322931 and mentioning a downregulation in miR-181b levels in SLE patients due to rs322931 CT /TT genotype compared with normal individuals once again noted the importance of ncRNAs in SLE. Due to the effects of SNPs and their correlation with microRNAs, the association of autophagy-related gene, MTMR3 SNP rs12537, which is the main target gene of miR-181-a, has been investigated with SLE progression.…”
Section: The Role Of Micrornas In the Development Of Slementioning
confidence: 97%
“…Although IFNA1 rs1332190 and rs10811543 alone were not significantly related to SLE, a combined analysis of these three factors simultaneously augmented the risk of disease progression. Therefore, He et al , 109 finding a correlation between miR-181b expression and rs322931 and mentioning a downregulation in miR-181b levels in SLE patients due to rs322931 CT /TT genotype compared with normal individuals once again noted the importance of ncRNAs in SLE. Due to the effects of SNPs and their correlation with microRNAs, the association of autophagy-related gene, MTMR3 SNP rs12537, which is the main target gene of miR-181-a, has been investigated with SLE progression.…”
Section: The Role Of Micrornas In the Development Of Slementioning
confidence: 97%
“…Within the past 13 years, genome-wide association and pathway-centered sequencing studies have identified many polymorphisms in interferon pathway genes that predispose an individual to developing SLE, including polymorphisms affecting the STAT4 , IRF3 , and IFNA1 genes [ 70 , 71 , 72 , 73 , 74 ]. While single polymorphisms may not be sufficient to cause autoimmunity alone, accumulating numbers of risk variants may cause the immune system to become overwhelmed, leading to immune dysregulation [ 24 , 75 ].…”
Section: The Interferon Pathway and Its Role In Autoimmunity: Systemic Lupus Erythematosus And Beyondmentioning
confidence: 99%
“…[13][14][15][16] Recently, some studies found that mi-croRNAs were involved in different types of autoimmune diseases, including SLE. [17][18][19][20] The miR-21 is considered a prospective marker and has been identified in many autoimmune diseases. 21 Some evidence has revealed that higher miR-21 expression can be found in lupus when compared with control groups.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that microRNA‐21 ( miR‐21 ) is involved in different kinds of diseases, such as cancers, diabetes, and neurological diseases 13–16 . Recently, some studies found that microRNAs were involved in different types of autoimmune diseases, including SLE 17–20 . The miR‐21 is considered a prospective marker and has been identified in many autoimmune diseases 21 .…”
Section: Introductionmentioning
confidence: 99%